Social Mobility of Military Afromestizos in the Independence and Civil Wars in Río de la Plata. Lorenzo Barcala (1795-1835) - Morales, Orlando Gabriel; Caballero, Luis César (Universidad Pedagógica y Tecnológica de Colombia, 2018)
This article reconstructs the biography of Lorenzo Barcala, a pardo born at the end of the XVIII century in Mendoza (in the capital context of the province of Cuyo), who played an important role in the non-white participation in civic and and other armed forces of the city between 1814 and 1835. Through Barcala´s case, it is possible to explore the social mobility of soldiers of African origin incorporated into military forces during the war of Independence and the civil wars of the current Argentine Republic, based on the hypothesis that their participation favored integration and social ascent. In this context, historiographic research interpellates and establishes relations between heterogeneous documental sources, that allow for the reconstruction of biographical events and their qualitative analysis, which focus on the agent and his practices, attempting to situate the trajectory of Barcala within the social history of the negro population in Mendoza. In favor of this idea, the biographical resource employed reveals Barcala´s strategies of manumission and family coniguration, evaluates the incidence of the prest in the access to property, and analyzes the extent of social relations and prestige in the economic commitments of the coronel.